Statistical analysis and degradation pathway modeling of photovoltaic minimodules with varied packaging strategies - Sameera Nalin Venkat; Sameera Nalin Venkat; Xuanji Yu; Xuanji Yu; Jiqi Liu; Jiqi Liu; Jakob Wegmueller; Jayvic Cristian Jimenez; Jayvic Cristian Jimenez; Erika I. Barcelos; Erika I. Barcelos; Hein Htet Aung; et al. (Frontiers in Energy Research, 2023)
Degradation pathway models constructed using network structural equation modeling (netSEM) are used to study degradation modes and pathways active in photovoltaic (PV) system variants in exposure conditions of high humidity and temperature. This data-driven modeling technique enables the exploration of simultaneous pairwise and multiple regression relationships between variables in which several degradation modes are active in specific variants and exposure conditions. Durable and degrading variants are identified from the netSEM degradation mechanisms and pathways, along with potential ways to mitigate these pathways. A combination of domain knowledge and netSEM modeling shows that corrosion is the primary cause of the power loss in these glass/backsheet PV minimodules. We show successful implementation of netSEM to elucidate the relationships between variables in PV systems and predict a specific service lifetime. The results from pairwise relationships and multiple regression show consistency. This work presents a greater opportunity to be expanded to other materials systems.